The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/etc.4450
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Multiclass Contaminants of Emerging Concern in Sediments by Liquid Chromatography with Tandem Quadrupole Mass Spectrometry

Abstract: A quick, easy, cheap, effective, rugged, and safe (QuEChERS)‐based extraction and simultaneous dispersive solid‐phase extraction (dSPE) clean‐up method was developed for contaminants of emerging concern (CECs) in sediment samples. Hydration with a phosphate buffer (pH 2.0) and salting out with NaCl and MgSO4 facilitated the extraction and liquid–liquid portioning of the aqueous and organic phases. Cleanup of the extracts was achieved by florisil and C18 (1:1) sorbents in dSPE with minimal compromise of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Residues of gemfibrozil, parabens, ketoprofen, fenoprofen, naproxen, diclofenac, carbamazepine, miconazole, sildenafil citrate, benzophenone-3, glibenclamide, and bisphenol analogues were detected in the sediments sampled from Lagoon Yundang (Xiamen, China) (Rashid, Wang, Li, Yu, & Sun, 2019).…”
Section: Sedimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Residues of gemfibrozil, parabens, ketoprofen, fenoprofen, naproxen, diclofenac, carbamazepine, miconazole, sildenafil citrate, benzophenone-3, glibenclamide, and bisphenol analogues were detected in the sediments sampled from Lagoon Yundang (Xiamen, China) (Rashid, Wang, Li, Yu, & Sun, 2019).…”
Section: Sedimentsmentioning
confidence: 99%
“…In recent years, QuEChERS has been considered as one of the novel techniques applied to determine CECs, which comprises both extraction and clean-up steps for complex matrices in environment and provides benefits including shorter time-consuming (quick and easy), less amount of organic solvent use (cheap and safe), high selectivity, and desirable recoveries (rugged). Rashid et al (2019) developed a QuEChERS-based extraction and simultaneous dispersive solid-phase extraction (dSPE) clean-up method for the determination of CECs in sediment. They treated the samples by hydration with phosphate buffer (pH = 2.0) and then salting out with NaCl and MgSO 4 and demonstrated that these procedures facilitated the extraction and the liquid-liquid portioning of the organic and aqueous phases and liquid-liquid portioning, and subsequently made the extracts well prepared for LC-MS/MS determination.…”
Section: Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivers, being the intermediaries between terrestrial and marine environments, serve as primary sinks for the outcomes of geogenic and anthropogenic activities. They are constantly exposed to a variety of pollutants released directly from the urban communities, via runoff from agricultural farms, or via effluents from wastewater treatment plants. , In this regard, contaminants of emerging concern (CECs) that include pharmaceutical and personal care products (PPCPs) and endocrine-disrupting chemicals (EDCs) are increasingly documented for the real and potential implications on environmental and human health. , CECs may persist in the environment and lead to problems like bioaccumulation, antibiotic resistance, endocrine disruption, and environmental/ecosystem pollution and degradation, which has implications for productivity . In some instances, CECs have been related to water quality attributes of industrial and municipal wastewater, agricultural surface runoff, aquaculture, and more .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this regard, contaminants of emerging concern (CECs) that include pharmaceutical and personal care products (PPCPs) and endocrine-disrupting chemicals (EDCs) are increasingly documented for the real and potential implications on environmental and human health. 3,4 CECs may persist in the environment and lead to problems like bioaccumulation, antibiotic resistance, endocrine disruption, and environmental/ ecosystem pollution and degradation, which has implications for productivity. 5 In some instances, CECs have been related to water quality attributes of industrial and municipal wastewater, agricultural surface runoff, aquaculture, and more.…”
Section: Introductionmentioning
confidence: 99%